Pseudo – Normal Operators - Naoum, Adil; Nassir, Sadiq (Iraqi Journal of Science, 2025)
In this paper we introduce a class of operators on a Hilbert space that contains properly the classes of normal operator, hyponormal operators, M – hyponormal operators, *- paranormal operators and dominat operators. We also give some properties of these operators. We call these operators Pseudonormal.